Geological map of Athens Metropolitan Area, Attica (Greece): A review based on Athens Metro ground investigation data - Boronkay, Konstantinos; Stoumpos, Georgios; Benissi, Maria; Rovolis, Georgios; Korkaris, Konstantinos; Papastamatiou, Despina; Dimitriou, Georgios; Chrysikopoulou, Anastasia; Miliotis, Ioannis; Giakoumis, Aristidis; Novack, Mark; Marinos, Paul (Bulletin of the Geological Society of Greece, 2021)
The ground investigations for the construction of Athens Metro –including over 60.000 m of sampling boreholes and geological mapping of the underground tunnel face–, planned and carried out under the supervision of ATTIKO METRO S.A., offer important geological data that enrich and locally modify our knowledge for the geology of Athens Metropolitan Area (AMA). On the basis of these data, this paper presents the Geological Map of AMA as well as a revised tectonostratigraphic scheme for the area and geological profiles along several sections of the Athens Metro lines. The geological map is a synthesis of the geological data obtained from the ground investigations with the already published geological maps and includes a Mesozoic rock assemblage as well as the Neogene-Quaternary Athens Basin. The following basic conclusions can be drawn from the interpretation of these data: (a) The Athens Unit, the basement of AMA, is divided into four formations (from bottom to top), the Lower Athens Schist, the Upper Athens Schist, the Athens Sandstone-Marl Series and the Crest Limestone. (b) Ultrabasic rocks (serpentinite) constitute the basement of Athens Unit. (c) Serpentinite bodies at the eastern border of Athens Basin, have undergone almost complete metasomatism to listwanite along their tectonic contacts with Alepovouni Marble on top and Kessariani Dolomite at their base. (d) The limestone outcrops at the western border of Athens Basin (e.g., Karavas hill) form tectonic windows of Pelagonian Upper Cretaceous limestone underneath the Athens Schist and not klippen of Crest Limestone on top of it. The revised geological map also includes the Attica-Evia Fault, which is the dominant structure of the broader area, locally mapped by two sampling boreholes across the planned metro line 4.